شهر عريضة افتتاح الدعاوى العقارية في التشريع الجزائري (قراءة في نص المادة 35 من القانون 18-18 المتضمن قانون المالية لسنة 2019) - العياشي, سراتي; باديس, سعودي (Université de M'sila, 2020)
ملخص: أوجب المشرع الجزائري شهر عريضة افتتاح الدعاوى العقارية بالسجل العقاري، بعد قيدها بأمانة ضبط المحكمة وفقا لأحكام المادة 85 من المرسوم التنفيذي 76-63 المتضمن تأسيس السجل العقاري، غير أن ذلك خلق نقاشا حادا بين المتعاملين في الشأن القضائي حول اعتبار شهر عريضة افتتاح الدعوى شرطا لقبول الدعوى أم قيد على رفعها؟ وبقى موقف القضاء متأرجحا بين مؤيد لشهر العريضة كإجراء إجباري وبين من يعتبره عملية إجرائية اختيارية، غير أن الواقع العملي أثبت رجاحة الرأي المؤيد لإجبارية إشهارها حماية للمتعاملين المحتملين في العقارات المتنازع فيها، وبصدور القانون 08-09 المتضمن قانون الإجراءات المدنية والإدارية انحاز المشرع صراحة إلى الرأي المؤيد لإجبارية إشهار العريضة أين جعل منها أحد أسباب عدم قبول الدعوى شكلا، كما حدد المشرع على سبيل الحصر مواضيع الدعاوى الواجبة الإشهار وذلك من خلال المادة 519 منه، غير أن المشرع لم يتطرق إلى تبعات هذا الإشهار سواء بالنسبة للتصرفات أو إلى آليات شهرها وشطبها من السجل العقاري وذلك إلى غاية استحداث المشرع للمادة 16 مكرر من الأمر 75-74 المتضمن إعداد المسح العام للأراضي وتأسيس السجل العقاري وذلك بموجب المادة 35 من القانون 18-18 المتضمن قانون المالية لسنة 2019. الكلمات المفتاحية: الدعاوى العقارية؛ السجل العقاري؛ شطب الدعوى؛ حكم قضائي؛ الحق العيني Abstract: The Algerian legislator has made the publication of the introductory motion requesting in the land register obligatory after its transcription in the courts administration service in accordance with the provisions of article 85 of the executive decree 76-63 establishing the Land Register but this has provoked a debate between the operators in the legal field since the publicity of an application initiating an action is a condition to declare the admissibility of the action or a condition to introduce it? The position of justice remained between those who are for the publicity of the request, as a mandatory procedure and those who consider it an optional transaction, but the operative fact has proved that the obligation of its advertising is more important to protect the operators in the land litigious object. By the promulgation of Law 08-09 containing the Code of Civil and Administrative Procedures, the legislator opted for the opinion which adopted the obligation to publicize the request, and which considered it one of the reasons for the inadmissibility of the action in form. The legislator, exclusively, set the objects of the action to be published by Article 519, but he did not deal with the consequences of this advertising either for the acts or for the mechanisms of his advertising or his deletion of the land register until the creation of article 16 A of the order 75-74 establishing the general survey and the institution of the land register under the article 35 of the law 18-18 containing finance law for the 2019 fiscal year. Key words: lawsuit property; land register; cancellation of the action; judgment; substantive law.
Keywords: الكلمات المفتاحية: الدعاوى العقارية؛ السجل العقاري؛ شطب الدعوى؛ حكم قضائي؛ الحق العيني ; Key words: lawsuit property; land register; cancellation of the action; judgment; substantive law